2008
DOI: 10.1111/j.1439-0426.2007.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine colonization, population structure and nursery functioning for 0-group sea bass (Dicentrarchus labrax), flounder (Platichthys flesus) and sole (Solea solea) in a mesotidal temperate estuary

Abstract: Estuarine colonization, population structure and nursery functioning for 0-group sea bass (Dicentrarchus labrax), flounder (Platichthys flesus) and sole (Solea solea) in a mesotidal temperate estuary SummaryThe function of the Mondego estuary as a fish nursery habitat was investigated from June 2003 to June 2004 by comparing the timing of estuarine colonization with juveniles of sea bass Dicentrarchus labrax, flounder Platichthys flesus, and sole Solea solea, while also analysing their population structure, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…The results for sole are particularly indicative of how this mechanism may act: in the beginning of the growing season, the RG of sole is higher in southern compared with northern areas; however, throughout the season this pattern inverses. In contrast to northern European areas where sole only occur after plaice and flounder have settled (Jager et al 1995, Amara et al 2001, Van der Veer et al 2001a, in southern European nurseries, sole juveniles are the first marine species to colonize these areas, appearing in April−May (Cabral 2003, Dolbeth et al 2010, and in some years, young-of-the-year can even be observed from late January onwards (Martinho et al 2008). This could confer an advantage to sole by occupying an empty niche with ample food resources, which, combined with high summer temperatures, would allow for fast growth.…”
Section: Latitudinal Trendsmentioning
confidence: 97%
“…The results for sole are particularly indicative of how this mechanism may act: in the beginning of the growing season, the RG of sole is higher in southern compared with northern areas; however, throughout the season this pattern inverses. In contrast to northern European areas where sole only occur after plaice and flounder have settled (Jager et al 1995, Amara et al 2001, Van der Veer et al 2001a, in southern European nurseries, sole juveniles are the first marine species to colonize these areas, appearing in April−May (Cabral 2003, Dolbeth et al 2010, and in some years, young-of-the-year can even be observed from late January onwards (Martinho et al 2008). This could confer an advantage to sole by occupying an empty niche with ample food resources, which, combined with high summer temperatures, would allow for fast growth.…”
Section: Latitudinal Trendsmentioning
confidence: 97%
“…The food chain of the Mondego estuary supports an important fish community (Martinho et al 2007). Studies performed by Martinho et al (2008) and Dolbeth et al (2008), who analyzed the feeding ecology of the main fish community, concluded that copepods were an important component of the fish diet. As a result, DVM behavior could lead to important trophodynamic effects in the fish community.…”
Section: Discussionmentioning
confidence: 99%
“…Data on abundance of 0-group juveniles were plotted from the original trawl data matrix according to Dolbeth et al (2008) and Martinho et al (2008) who determined that only one cohort is produced each year. Fish abundance (individuals per 1000 m 2 ) was determined as the number of 0-group fish caught in the total sampled area.…”
Section: Discussionmentioning
confidence: 99%
“…From each yearly cohort, the abundance of the first three months when estuarine catches start were chosen, since they represented the onset of the 0-group settlement period; at this time, fish are approximately three months old. In general, Solea solea's recruitment to estuarine waters starts in the winter, whereas for Platichthys flesus and Dicentrarchus labrax the recruitment usually starts in early and late spring, respectively (Dolbeth et al, 2008;Martinho et al, 2008). The environmental parameters were obtained on the third month prior to the first estuarine catch, based on their expected influence on the colonization process.…”
Section: Discussionmentioning
confidence: 99%